Meta-analysis: effects of mental preparation techniques based on imagery - hypnosis on flow states and athletic performance - Garzón Mosquera, Julián Camilo (2020)
The present study aims to examine the effectiveness of psychological mental preparation techniques based on imagery or hypnosis on the state of flow, sports performance, and their relationship using the meta-analytic technique. A literature review was conducted in ten databases from August to October 2017, which resulted in 17 studies related to sports activities with pretest-posttest measurements. The Effect Size (ES) of mean difference was analyzed using a random model. A total of 53 ESs and 62 ESs were obtained for flow states and performance, respectively. A positive ES was found for the flow state (ES = .782, n = 52, p <.001) and for performance (ES = .339; n = 60; p <.05), and a positive relationship was verified between the two variables (ρ = .312, p <.05). The most relevant variables that moderate the effect size of the flow state and performance are age, years of sports experience, and sex. It is concluded that imagery is the most effective psychological technique to increase the state of flow and performance. Further research with a pure experimental design considering the multi-dimensional measurement of the state of flow is recommended.